Army science and technology for homeland security. (National Academies Press, 2004)
"Shortly after the events of September 11, 2001, the U.S. Army asked the National Research Council (NRC) for a series of reports on how science and technology could assist the Army meet its Homeland defense obligations. The first report, Science and Technology for Army Homeland Security Report 1, presented a survey of a road range of technologies and recommended applying Future Force technologies to homeland security wherever possible. In particular, the report noted that the Army should play a major role in providing emergency command, control, communications, computers, intelligence, surveillance, and reconnaissance (C4ISR) capabilities and that the technology and architecture needed for homeland security C4ISR was compatible with that of the Army s Future Force. This second report focuses on C4ISR and how it can facilitate the Army s efforts to assist the Department of Homeland Security (DHS) and emergency responders meet a catastrophic event."--Publisher's website